Formulation of Settlement of Criminal Cases of Drug Addicts by Prosecutors Using a Restorative Justice Approach - Rischy Akbar Santosa (Jurnal Hukum Khaira Ummah, 2025)
Abstract. Attorney General's Guideline Number 18 of 2021 concerning the Settlement of Narcotics Abuse Criminal Cases Through Rehabilitation with a Restorative Justice Approach as Implementation of the Principles Mr. Litis Prosecutor. This Prosecutor's Guide emphasizes restorative justice, prioritizing rehabilitation over incarceration for drug users. The purpose of this study is to analyze and identify the current approach to drug addiction cases handled by prosecutors. To analyze and identify weaknesses in the current approach to drug addiction cases handled by prosecutors. To identify a formulation for resolving drug addiction cases by prosecutors using a restorative justice approach. This thesis is written using the theory of restorative justice, the theory of legal systems and progressive legal theory, the sociological juridical approach method, the research specifications are descriptive analysis, the data sources consist of primary data and secondary data taken from primary legal materials, secondary legal materials, tertiary legal materials, data collection techniques through observation and interviews. The results of the study show that the resolution of drug addict criminal cases by prosecutors is currently guided by Guideline Number 18 of 2021, which is a new reference for public prosecutors to optimize the resolution of drug abuse criminal cases through rehabilitation with a restorative justice approach as an implementation of the principle the owner of the suit Prosecutors. There needs to be alignment and harmonization between these guidelines and various laws and regulations. Weaknesses in the legal structure include limited human resources, very limited availability of rehabilitation facilities, and a lack of operational funds. Weaknesses in the legal substance include the unclear norms of Narcotics Law Number 35 of 2009 concerning narcotics, and the absence of a law that explicitly authorizes the prosecutor's office to carry out rehabilitative measures at the prosecution stage. Weaknesses in the legal culture include a lack of public knowledge about rehabilitation, users' fear of being imprisoned, and concerns about family reputation. The formulation of drug addict criminal cases by prosecutors using a restorative justice approach, namely through alignment and harmonization between Prosecutor's Guideline Number 18 of 2021 concerning the Settlement of Narcotics Abuse Criminal Cases Through Rehabilitation and a Restorative Justice Approach as the Implementation of the Principles Mr. Litis with the Criminal Procedure Code.